Xamarin blueprints leverage the power of Xamarin to create stunning cross-platform and native apps - Williams, Michael (Packt Publishing, 2016)
Leverage the power of Xamarin to create stunning cross-platform and native apps About This Book Helps you get a clear practical understanding of creating professional-grade apps with Xamarin Covers Xamarin.Forms, Xamarin Android, and Xamarin iOS If you want to transform yourself from an amateur mobile developer into a professional app developer across multiple platforms, then this is the ideal book for you Who This Book Is For If you are a mobile developer looking to create interesting and fully featured apps for different platforms, then this book is the ideal solution for you. A basic knowledge of Xamarin and C# programming is assumed What You Will Learn Discover eight different ways to create your own Xamarin applications Improve app performance by using SQLite for data-intensive applications Set up a simple web service to feed JSON data into mobile applications Store files locally with Xamarin.Forms using dependency services Use Xamarin extension libraries to create effective applications with less coding In Detail Do you want to create powerful, efficient, and independent apps from scratch that will leverage the Xamarin framework and code with C#? Well, look no further; you've come to the right place! This is a learn-as-you-build practical guide to building eight full-fledged applications using Xamarin.Forms, Xamarin Android, and Xamarin iOS. Each chapter includes a project, takes you through the process of building applications (such as a gallery Application, a text-to-speech service app, a GPS locator app, and a stock market app), and will show you how to deploy the application's source code to a Google Cloud Source Repository. Other practical projects include a chat and a media-editing app, as well as other examples fit to adorn any developer's utility belt. In the course of building applications, this book will teach you how to design and prototype professional-grade applications implementing performance and security considerations. Style and approach A project-based approach that will solve all your needs when it comes to creating native Android, iOS, and cross-platform apps efficiently and effectively.
Online resource; title from PDF title page (EBSCO, viewed November 16, 2016)
Keywords: iOS (Electronic resource); Android (Electronic resource); Xamarin studio (Computer file); Mobile apps; C# (Computer program language); Applications mobiles; C# (Langage de programmation); COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference